STUDENTS’ PERCEPTION ON THE USE OF GOOGLE TRANSLATE IN INCREASING THEIR VOCABULARY MASTERY - Kurniawan Saputra; Baso Jabu; Chairil Anwar Korompot (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2023)
This study aims to determine the students’ perceptions of Google Translate in improving their vocabulary mastery. A quantitative method design was used in this study. The population of this research is the students at the English Education Study Program, Faculty of Languages and Literature, Universitas Negeri Makassar in the academic year 2022-2023. The instrument of this research was a questionnaire. To achieve this, data are collected in the form of a Likert questionnaire. The samples of the questionnaire are 35 students. The research findings showed that there are 13 (38%) students are classified as very positive, 13 (38%) students are classified as positive, 3 (8%) students are classified as moderate, 4 (11 %) students are classified as negative and 2 (5%) students are classified as very negative. Based on the data, it can be concluded that students have positive perception on the use of Google Translate in increasing their vocabulary mastery. Keywords         Students Perception, Google Translate, Vocabulary Mastery